Cross-Cultural Approach to the Study of Self-Regulatory Personality Predictors of Aggression - Banshchikova T.N; Fomina E.A; Morosanova V.I (Moscow State University of Psychology and Education, 2018)
The paper presents data of an empirical study of the relationship between aggressive manifestations and self-regulatory personality characteristics of teachers. It is assumed that the features of aggressive manifestations are determined by personal characteristics and the cultural context of the teachers' lives. The level of self-regulation development is also shaped by sociocultural conditions. The study involved 278 teachers aged 20-72 years from the Stavropol and Krasnodar territories and from the republics of North Ossetia-Alania, Karachaevo-Cherkessia, and Kabardino-Balkaria. The system of research methods was based on the integration of nomothetic and ideographic approaches and included observation and psychological testing. The study revealed certain differences in aggressive manifestations among the respondents from different regions of southern Russia. It was found that the level of conscious self-regulation development is not an invariant and has its cross-cultural specifics. Indicators of conscious self-regulation (planning, evaluation of results), racial tolerance and restraint in risk situations are significant predictors of aggression management.